2018
DOI: 10.1111/1750-3841.14005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Astaxanthin in Oil‐in‐Water Emulsions with Differently‐Charged Emulsifiers Under Chlorophyll Photosensitization

Abstract: Astaxanthin is a lipid-soluble pigment and has antioxidant, anticancer, and anti-inflammatory properties and beneficial effects on cardiovascular diseases. Many lipid-based foods are displayed on the shelves in the markets under fluorescent light. The addition of astaxanthin can extend the shelf life of O/W emulsion type foods such as beverage and dressing products under visible light irradiation. Also, oxidative stability in emulsion type foods containing astaxanthin rich natural ingredients can be predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It has been reported that for testing antioxidant activity/capacity of natural compounds in the targeted samples, multi in vitro antioxidant test models that measure the electron or hydrogen atom transfer from antioxidant compounds to free radicals (reactive oxygen or reactive nitrogen species), must be used [ 66 , 67 , 68 ]. Moreover, quantification of total phenolic, total flavonoid by colorimetric methods, and determination of antioxidant activity using in vitro antioxidant assays are very useful approaches to evaluate the health beneficial potential, and for the quality control of food materials, and natural products [ 69 , 70 , 71 ]. Therefore, in the present study, free radicals’ inhibition or antioxidant potential in the bulbs and leaves of nine varieties of onion, planted at three diverse locations was evaluated using various assays viz.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that for testing antioxidant activity/capacity of natural compounds in the targeted samples, multi in vitro antioxidant test models that measure the electron or hydrogen atom transfer from antioxidant compounds to free radicals (reactive oxygen or reactive nitrogen species), must be used [ 66 , 67 , 68 ]. Moreover, quantification of total phenolic, total flavonoid by colorimetric methods, and determination of antioxidant activity using in vitro antioxidant assays are very useful approaches to evaluate the health beneficial potential, and for the quality control of food materials, and natural products [ 69 , 70 , 71 ]. Therefore, in the present study, free radicals’ inhibition or antioxidant potential in the bulbs and leaves of nine varieties of onion, planted at three diverse locations was evaluated using various assays viz.…”
Section: Resultsmentioning
confidence: 99%
“…In the area of active packaging, radical scavenging assays can contribute to assessing efficiency of antioxidant packaging formulations [169]. The in vitro methodologies for antioxidant and TPC assays are applied in routine quality control programs by food companies in many countries [170,171]. The methodologies for antioxidant and TPC assays can be considered valuable high-throughput, low cost tools used to evaluate and find antioxidant sources and for quality control of foods and natural products.…”
Section: Author Detailsmentioning
confidence: 99%
“…FUC is present in brown seaweeds belonging among others to the genera Dictyota, Ecklonia, Fucus, Hijikia, Laminaria, Petalonia, Sargassum, Scytosiphon, Sphaerotrichia, and Undaria [7][8][9][10][11][12]. Many studies showed that AST and FUC have antioxidant [12][13][14][15][16], antiinflammatory [14,[17][18][19][20], and anticancer [21][22][23][24][25] activities. It was also demonstrated that these phycochemical constituents have anti-diabetic [26,27], anti-obesity [28][29][30], and neuroprotective effects [31][32][33].…”
Section: Introductionmentioning
confidence: 99%